Places of Pain : Forced Displacement, Popular Memory and Trans-local Identities in Bosnian War-torn Communities. - Halilovich, Hariz (Space and place., 2013)
For displaced persons, memory and identity is performed, (re)constructed and (re)negotiated daily. Forced displacement radically reshapes identity, with results ranging from successful hybridization to feelings of permanent misplacement. This compelling and intimate description of places of pain and (be)longing that were lost during the 1992-95 war in Bosnia and Herzegovina, as well as of survivors' places of resettlement in Australia, Europe and North America, serves as a powerful illustration of the complex interplay between place, memory and identity. It is even more the case when those.